Re-interpreting Memory of History by Fragmented Continuum Concept in Museum Design - Nisita Hapsari; Nur Endah Nuffida (Jurnal Sains dan Seni ITS, 2018)
Architecture has always been considered as a carrier of messages. Stories and buildings have been tied up together since the beginning of the conscious formation of space and the first attempts to understand the world around us. Architecture that has been ruined or abandoned is also has the same condition. The 'death' could be a new beginning for buildings. An example that still exists in the present is Kedung Cowek Fort. Kedung Cowek Fort is a witness of history that still exists. The design problem which will be proposed in this final project is how the ruins of architecture could be 'revived'. Architect also responsible to how the space could be an instrument which people could experience the memory of history from the event of the past with universal language which people in the present could understand. By using historicism approach, what already happened in the past become a background for the design and by using meaning in architecture approach, those past events are interpreted to story. The tool to transfer the story into architectural design is narrative method. The building type proposed in this final project is historical museum. By giving the interpretation of historical background, people could try to understand the history from the perspective and story architect creates. In this case, history is defined as a fragmented continuum story.